HUBUNGAN KESEJAHTERAAN SPIRITUAL DENGAN KESEHATAN MENTAL MAHASISWA PRODI KESEHATAN DI UNIVERSITAS MUHAMMADIYAH KLATEN - Arlina Dhian Sulistyowati; Yunisya Adelia (MOTORIK Jurnal Ilmu Kesehatan, 2025)
College students are an early adult age group that is vulnerable to psychological stress due to life transitions and academic demands. Spiritual well-being is believed to play an important role in supporting mental health, especially in an Islamic-based university environment that emphasizes the development of spiritual and moral values. However, the relationship between spiritual well-being and mental health of students, especially in the Health Study Program at Muhammadiyah University of Klaten has not been studied empirically. This study aims to determine the relationship between spiritual well-being and mental health in students of the Health Study Program at Muhammadiyah University of Klaten. This study used a quantitative design with a cross-sectional approach. The research sample was students of the Health Study Program at Universitas Muhammadiyah Klaten who were selected by stratified random sampling. The instruments used included the Daily Spiritual Experience Scale (DSES) questionnaire to measure spiritual well-being and the Self Reporting Questionnaire (SRQ) to assess mental health. Data were analyzed univariately and bivariately using the spearman rank statistical test. It was found that out of 161 respondents (100%) there were 3 students who had low spiritual well-being (1.9%), respondents who experienced moderate spiritual well-being were 46 students (28.6%), and respondents who had high spiritual well-being were 112 students (69.6%). Respondents who had a healthy mental health category were 100 students (62.1%) while those who had mental emotional disorders were 61 students (37.9%). The results of the spearman rank test analysis significant value (p) value 0.000 (α=0.05) with (r) 0.844. The conclusion of this study is that there is a significant relationship between the level of spiritual well-being and mental health in health study program students.